Awareness of Breast Cancer among the Secondary Level Adolescent Girls Student in Kathmandu, Nepal - G.C., Bishnu (JMC Research Journal, 2023)
The study entitled "Views on awareness of breast cancer among the secondary level adolescent girl" was based on descriptive research design and qualitative study with focus group discussion method. Only 8 adolescent girl students from grade XI and XII with in the Janamaitri Multiple Campus, Kathmandu were selected purposively for discussion. The student’s views on awareness of breast cancer were analyzed thematically by FGD guidelines. It is found that the adolescent girls have positive knowledge and perception on breast cancer but diversity of knowledge of basic causes of breast cancer based on scientific as well myth. They had good knowledge on initial sign and symptoms on breast cancer but they do not have their own live experience about it. They were in the favors of breast self-examination practices but still ignorance in what, why and how it can be practices properly. They were not familiar on detection of sign and symptoms of breast cancer properly. Some have faced the live experience of breast cancer in their family members but they do not have their own live experience. They revealed that the proper health education and regular awareness program could prevent the secondary level adolescent girls from early breast cancer.